BOOK REVIEW: CIPRIAN PORUMBESCU NECUNOSCUT (CIPRIAN PORUMBESCU UNKNOWN), PUBLISHING BY ED. LIDANA, SUCEAVA, 3 EDIŢII, 2011-2013 (ISSN: 2284-712X) - COCA, Gabriela (Studia Universitatis Babes-Bolyai Musica, 2013)
In late May and early June of this year, organized by the Bucovina Cultural Center from Suceava, took place the third edition (2013) of the “Ciprian Porumbescu” European Festival of Arts, having among the guests of honour the Porumbescu’s family descendant, Mrs. Nina Cionca, author of a vast, detailed and richly illustrated monograph about Ciprian Porumbescu. Among a series of notable cultural representations made to celebrate 160 years of the birth of Bucovinean composer Ciprian Porumbescu, in June 1st at Stupca (today: Ciprian Porumbescu), at the Ciprian Porumbescu Memorial Museum, also held at the National Musicological Symposium. Within it have been presented the following papers dedicated to the composer's life and activity: Leca Morariu and the Monumental Monograph Worshiped to Ciprian Porumbescu (author: Vasile Vasile – from the University of Piteşti); The Architectural and Tonal Support of the Dramaturgy of the “Crai nou” (New Philanderer) Operetta by Ciprian Porumbescu (author: Gabriela Coca – from the Babeş-Bolyai University of Cluj-Napoca); “Balada” (The Ballad) of Ciprian Porumbescu – a Representative Creation of the Art Music of Bucovina (19th century) (author: Zamfira Dănilă – from the “George Enescu” Academy of Art - Iaşi); The Reception of Ciprian Porumbescu’s Creation in Banat (author: Constantin Tufan Stan – from the Filaret Barbu School of Fine Arts of Lugoj); „Altarul Mănăstirii Putna” (The Altar of Putna Monastery) (author: Sever Paraschiv Dumitrache – from the Bucovina Cultural Center of Suceava); and The Musicological Trilogy “Ciprian Porumbescu Unknown” to an end (autor: Constanţa Cristescu – from the Bucovina Cultural Center - Suceava). These papers are all included, in this presented volume, with other two studies: Ciprian Porumbescu – Friends and his Collaborators of Braşov (author: the regretted musicologist professor Constantin Catrina from the Transylvania University of Braşov) and The Aspects of the Musical Language and of its Architecture in Compositions by Ciprian Porumbescu (author: Ozana Kalmuski-Zarea – from the “Mihail Jora” Philharmonic of Bacău). In a special chapter, entitled Documenta, this volume contains the facsimile of the manuscript of the orchestra score of the vocal-symphonic work The Altar of Putna Monastery by Ciprian Porumbescu.